Rhetoric And Visual Metaphor Of “Aku Kartini” In A Context of Sculpture and Activism - Laras Shinta Prasetya; Aries Budi Marwanto (Texture : Art And Culture Journal, 2025)
This research aims to analyze the visual rhetoric elements and visual metaphors contained in Aku Kartini sculpture and connect them with the theme of activism. The statue titled Aku Kartini is one of the works from the Kartini series created by Budi Santoso, with the theme of activism as the object of this research. The sculpture presents another version of Kartini, an Indonesian heroine who is famous for her slogan “out of darkness comes light”. The research method used is descriptive qualitative, to collect data and explain the phenomenon of Aku Kartini sculpture, using Sonya K. Foss' rhetoric theory and Lakoff and Johnson's metaphor theory to explain the phenomenon of Aku Kartini sculpture in terms of rhetoric and metaphor. The research results show that the Aku Kartini sculpture possesses visual rhetoric characteristics, and its metaphorical meaning is closely related to the theme of activism presented during the exhibition.